The prevalence of COVID-19 among health care personnel in a University Hospital by the end of 2020, and ambient air CO2 in hospital rooms ventilated by window-opening in 2021/22 - Blinc, Aleš (Strojniški vestnik, 2022)
In autumn and winter 2020/21 and again in 2021/22 Slovenia has ranked among countries with the highest incidence of COVID-19 per million inhabitants and high excess mortality over the average of previous years. Many patients on non-COVID-19 hospital wards were in fact infected by SARS-CoV-2. Health care personnel at the University Medical Centre Ljubljana (UMCL) were falling ill by Covid-19 in large numbers despite wearing surgical masks and eye protection when dealing with patients. We compared the prevalence of COVID-19 among health care personnel of the Division of Internal Medicine, UMCL by the end of December 2020 with the national average of Slovenia. After instructions had been issued to increase room ventilation by opening windows every hour for at least 10 minutes, ambient air CO2 was measured in an intensive care room and in an outpatient clinic room during a 10-month period, from April 2021 to February 2022. The prevalence of COVID-19 by the end of December 2020 was 42 % among nurses, 21 % among registered nurses and 17 % among medical doctors, whereas the national of average of the population was significantly lower at 5.5 %. Between April 2021 and February 2022, the average CO2 (ppm) in the intensive care was 633 (standard deviation 198, range 376 – 1540), while in the outpatient clinic the average was 552 (standard deviation 199, range 380 - 1910). During 2020, before the instructions for the use of personal protective equipment were up-graded and before regular window-opening was advised, the prevalence of Covid-19 among health care personnel at the Division of Internal medicine, UMCL exceeded the national average by 3- to 8-fold. After regular window-opening was advised, the peak CO2 levels still often exceeded the recommended “safe” level of 750 ppm.
Keywords: aerogeno širjenje; airborne spread; CO2 level; Covid-19; excess mortality; koncentracija CO2; prezračevanje prostorov; razširjenost; room ventilation